2022
DOI: 10.1155/2022/1636839
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Therapeutic Effect and Prognosis of Danzhi Xiaoyao Powder Combined with Photodynamic Therapy in the Treatment of Rose Acne

Abstract: Background. Rose acne is a chronic inflammatory skin disease that can cause paroxysmal flushing, persistent erythema, papules or papules on the face, and pustules, and it has a greater impact on the life of patients, so it is important to treat it. Objective. To investigate the effect of Danzhi Xiaoyao Powder combined with photodynamic therapy (PDT) on the curative effect evaluation and prognosis of patients with rose acne. Patients and Methods. The clinical data of 110 rose acne patients who were treated in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…are often combined with PDT. Surgery, laser, and freezing eliminate macroscopic local lesions, while PDT eliminates extensive, occult lesions 24–30 …”
Section: Discussionmentioning
confidence: 99%
“…are often combined with PDT. Surgery, laser, and freezing eliminate macroscopic local lesions, while PDT eliminates extensive, occult lesions 24–30 …”
Section: Discussionmentioning
confidence: 99%
“…Future refinements of parameters hold promise for better outcomes. Recent randomized controlled trials with larger sample sizes have reported improved treatment efficacy and milder adverse reactions when PDT is combined with other modalities, such as 1550 nm fractional therapy laser or Danzhi Xiaoyao Powder [ 268 , 269 ]. In a single-arm trial involving 10 patients with ETR or PPR, PDT in combination with IPL also demonstrated favorable treatment outcomes and high patient satisfaction [ 270 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%